KEPRIBADIAN TOKOH CERPEN BURONAN KARYA AGUS NOOR DENGAN CERPEN POTONGAN TUBUH KARYA PYUN HYE-YOUNG: KAJIAN PSIKOANALISIS - Wisanti Wisanti; Dian Hartati (Aksara: Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2022)
The research aims to compare the short story "Fugitive" by Agus Noor and the short story translation "Body Pieces" by Pyun Hye-young. The study reviewed aspects of literary psychology in two literary works. Studies examine the psychology of the main character using descriptive qualitative methods. The results of the study: id on both short stories is to bring body parts and get news of the discovery of body parts; ego in both short stories is the character takes decisions from the problems faced; Superego is the acceptance of figures on the things that have been determined from the resolution of the problem. The two figures from the short story studied have behavioral similarities that are about facing murder cases, which distinguishes only the social and cultural background between domestic and foreign socio-cultures, namely South Korea.